2016
DOI: 10.1371/journal.pone.0164413
|View full text |Cite
|
Sign up to set email alerts
|

No Impact of Body Mass Index on Outcome in Stroke Patients Treated with IV Thrombolysis BMI and IV Thrombolysis Outcome

Abstract: Background and PurposeThe impact of excess body weight on prognosis after stroke is controversial. Many studies report higher survival rates in obese patients (“obesity paradox”). Recently, obesity has been linked to worse outcomes after intravenous (IV) thrombolysis, but the number and sample size of these studies were small. Here, we aimed to assess the relationship between body weight and stroke outcome after IV thrombolysis in a large cohort study.MethodsIn a prospective observational multicenter study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…A post hoc analysis of the MR CLEAN trial demonstrated that a shift toward a better functional outcome with higher body mass index, and mortality was inversely related to body mass index; 25 while some other studies showed no significant favorable effect, or negative effect of obesity on outcome after recanalization treatment. 26 , 27 Similarly, our present study did not find a significant association between increased waist circumference and clinical outcomes after EVT. This discrepancy might be due to the differences in study populations and study methods, especially in the definition of obesity.…”
Section: Discussionsupporting
confidence: 58%
“…A post hoc analysis of the MR CLEAN trial demonstrated that a shift toward a better functional outcome with higher body mass index, and mortality was inversely related to body mass index; 25 while some other studies showed no significant favorable effect, or negative effect of obesity on outcome after recanalization treatment. 26 , 27 Similarly, our present study did not find a significant association between increased waist circumference and clinical outcomes after EVT. This discrepancy might be due to the differences in study populations and study methods, especially in the definition of obesity.…”
Section: Discussionsupporting
confidence: 58%
“…Several observational studies point to a lower rate of stroke recurrence in overweight or obese patients (41)(42)(43)(44). However, recent studies in stroke patients receiving intravenous thrombolysis or patients with mild symptoms did not detect this relationship, thus challenging the "obesity paradox" (45,46). Obesity was more common among patients with multiple CS and PFO in a single study, though the recurrence risk was not independently associated with BMI (18).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, Diedler J et al reported that the risk of sICH significantly increased in patients weighing > 100 kg who accepted intravenous r-tPA thrombolysis compared to those weighing ≤ 100 kg [13]. However, a meta-analysis across three studies in Europe reported that obesity (BMI ≥ 30 kg/m 2 vs. BMI < 30 kg/m 2 ) was not related to sICH risk with 3-month follow-up [8,9], while others found inverse associations that may be related to obese patients receiving an intravenous r-tPA dose < 0.9 mg/kg [11]. These seemingly discrepant observations might be explained by differences in race, length of follow-up, sample size, or definition and subtype of HT.…”
Section: Discussionmentioning
confidence: 99%
“…BMI was calculated as weight in kilograms divided by height squared in meters. Body weight and height were measured by nurses or obtained from the patient or relatives or -if not available -from estimates made by the attending stroke physician [8][9][10].…”
Section: Baseline Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation